Penyaluran Zakat dalam Menanggulangi Kemiskinan (Studi Kasus Baznas Cilegon Tahun 2017-2018 - Fennty Septiani (Scimadly Publishing, 2023)
The National Amil Zakat Agency is an official body formed by the government domiciled in districts or cities and provinces whose task is to collect and distribute Zakat, Infaq and Sadaqah. The purpose of this study was to determine the distribution of zakat carried out by the National Amil Zakat Agency in an effort to reduce poverty in Cilegon City. This type of research is field research, namely research whose data sources are obtained directly from the Cilegon City National Amil Zakat Agency and the research method is qualitative. Zakat distribution carried out by the Amil Zakat Agency in Cilegon City is in the form of providing business capital that is used for mustahik which aims to improve mustahik welfare and reduce poverty in Cilegon City.